A pragmatics study on verbal abuse against women and children by Bengkulu communities on social-media, at schools, and in families - Irma Diani; Arono; Wisma Yunita (Universitas Muhammadiyah Malang, 2022)
This study aims to discuss verbal abuse against women and children on social media, at schools, and in families by Bengkulu communities in the coastal areas of the Bengkulu province. The verbal abuse was viewed in the use of the language based on pragmatic studies in terms of language functions, presuppositions and implicatures, language politeness, and the reaction of the community in every case of violence, especially family and society in this case family and society, in this case, social media. The design of this study was qualitative research with a phenomenology paradigm. This study involved 35 informants that spread on social media, at schools, and in families with a purposive sampling technique. The dataere gathered through documentation and covert observation. The data were analyzed in three stages: data reduction, data display, and conclusion drawing. The triangulation technique was done by involving experts in pragmatics and women activists. The results revealed that there were 35 data on verbal abuse with details of 10 data on verbal abuse on social media, 13 data on violent verbal abuse in the family environment, and 12 data on verbal violence at school that occurred in Bengkulu province in the last three years (2018-2020). The verbal abuses occurred in the form of disrespectful words, bullying, cyberbullying, words that are considered demeaning, insulting, intimidating, blasphemous, homophobic, sarcastic, yelling, cursing, ridiculing, yelling, slander, harsh words, scolding, and nagging excessively, cold, and humiliating in public.